Composite current collector
By introducing a porous support layer, conductive layer and fill layer structure into the composite fluid, especially by setting an expansion buffer on the side of the phase change layer, the problem of rising lithium battery temperature caused by poor thermal conductivity in the composite fluid is solved, and better heat dissipation and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411825794.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The thermal conductivity of the polymer support layer in the composite liquid collecting fluid is low, which causes the temperature of the lithium battery to rise rapidly during the large-scale charging and discharging process, affecting the service life and performance of the battery.
A composite fluid-collection structure is adopted for a porous support layer, a conductive layer and a filling layer, wherein the filling layer includes a phase change layer and a sealing layer, and an expansion buffer is present on the sides of the phase change layer to buffer volume expansion caused by solid-liquid phase change.
It improves the heat dissipation performance of the current collector, reduces the volume expansion problem caused by phase change, ensures mechanical and safety performance, and extends the service life of lithium batteries.
Smart Images

Figure CN119650712A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of current collectors, and in particular to a composite current collector. Background Art
[0002] In secondary batteries, a current collector is needed, which is the part that converges current and is generally made of aluminum foil or copper foil. In the prior art, for safety reasons, a composite current collector is proposed, which includes a polymer support layer and a metal layer arranged on both sides of the support layer. This can improve the safety of subsequent batteries. Compared with metal foil current collectors, this composite structure can also reduce the weight of the current collector and improve the energy density of lithium-ion batteries.
[0003] In the current composite current collector, due to the low thermal conductivity of the polymer support layer material, the battery temperature will rise rapidly during high-rate charge and discharge. Excessively high operating temperature will affect the service life and performance of the lithium battery.
[0004] Therefore, in order to use the battery under appropriate working conditions and ensure safety, the industry usually takes measures to introduce suitable functional materials (such as flame retardants, etc.) into the lithium-ion battery system. Since the relevant flame retardants or thermally conductive fillers are generally added to the polymer material, this places higher requirements on the preparation process of the support layer. For example, some functional particles have poor compatibility with the substrate, which can easily cause migration problems and form crystallization points, which in turn affect the flatness of the polymer support layer and easily cause the subsequent current collector metal layer to crack, which may further cause the active material layer of the electrode to crack and fall off. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a composite current collector that improves the safety performance of the support layer while ensuring the mechanical properties.
[0006] The technical solution of the present invention is as follows:
[0007] The present application discloses a composite current collector, comprising:
[0008] The support layer is a porous support layer having a plurality of holes inside;
[0009] A conductive layer is attached to the surface of the support layer;
[0010] and, a filling layer, which includes a phase change layer and a sealing layer arranged on the outer side of the phase change layer;
[0011] There is an expansion buffer zone on the side of the phase change layer to provide a buffer zone during the solid-liquid phase change.
[0012] Based on the above technical solution, the volume expansion problem caused by phase change can be improved, and at the same time, the heat dissipation performance of the current collector can also be improved.
[0013] Furthermore, the total thickness of the expansion buffer zone is set to 0.05-0.1 times the thickness of the phase change layer.
[0014] Based on the above technical solution, controlling the thickness of the expansion buffer zone appropriately can ensure a good thickness of the sealing layer, thereby ensuring the overall mechanical properties. At the same time, it can adapt to the volume change after the melting phase change and slow down the flow of the phase change material after melting caused by excessive voids.
[0015] Further, the expansion buffer is set to be a gap.
[0016] Based on the above technical solution, the gap is set to provide sufficient expansion space for the phase change layer.
[0017] Further, the expansion buffer is configured as an elastic layer.
[0018] Based on the above technical solution, the expansion buffer is set as elastic filling, which can ensure the overall mechanical strength and also reduce the void ratio, thereby reducing the flow of the phase change material after melting.
[0019] Furthermore, the elastic modulus of the elastic layer is less than or equal to 1000 MPa.
[0020] Based on the above technical solution, the buffering deformation capability of the formed elastic layer can be guaranteed.
[0021] Furthermore, the elastic layer is formed by evaporating the elastic material dispersion under a vacuum environment.
[0022] Based on the above technical solution, the dispersibility and filling property of the elastic particles in the elastic layer can be increased; and the particles in the elastic layer can be easily distributed on the surface of the phase change material layer.
[0023] Further, the thickness of the support layer is 3.5-300 μm;
[0024] And / or, the pore size of the porous material is 0.05-1 mm.
[0025] Furthermore, the holes of the support layer are blind holes or through holes.
[0026] Furthermore, the holes may be interconnected.
[0027] Furthermore, the support layer is configured as a three-dimensional structured foam metal with a porosity of 80%-95%;
[0028] Alternatively, the support layer is configured as a metal mesh layer.
[0029] Based on the above technical solution, a connected through-hole structure is provided to increase the mutual mechanical interlocking with the filling layer and increase the anchoring force.
[0030] Furthermore, the phase change latent heat of the phase change layer is preferably greater than 120 J / g.
[0031] Based on the above technical solution, the performance of the phase change material can be guaranteed and the system temperature can be more easily controlled.
[0032] Furthermore, the phase change temperature of the phase change layer is between 45°C and 65°C.
[0033] Based on the above technical solution, the phase change temperature of the phase change layer is within an appropriate range, which is more suitable for the safe temperature range of subsequent batteries. It can also reduce the number of volume increases caused by the melting phase change and reduce the frequency of volume expansion, thereby reducing the impact of expansion on the system.
[0034] Furthermore, the thickness of the phase change layer when solidified is 0.4-0.7 times the thickness of the filling layer.
[0035] Based on the above technical solution, the amount of phase change material can be guaranteed, so as to give full play to the performance of the phase change material, while taking into account the overall performance of the film.
[0036] Furthermore, the phase change layer is formed in the support layer based on a tape casting method.
[0037] Furthermore, the sealing layer material includes a polymer material.
[0038] Based on the above technical solution, it is convenient to fill the sealing layer into the supporting layer.
[0039] Furthermore, the sealing layer is compounded in the supporting layer by hot pressing.
[0040] Based on the above technical solution, the sealing layer material can be conveniently melted and then pressure is exerted to form a sealing layer in the supporting layer.
[0041] Furthermore, the thickness of the conductive layer is 0.1-2.0 μm.
[0042] Furthermore, the conductive layer is made of one or a combination of copper, aluminum, nickel, chromium, gold and silver. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0044] Figure 1 It is a schematic diagram of the structure of setting a double-layer sealing layer;
[0045] Figure 2It is a schematic diagram of the structure of setting a single-layer enclosed layer;
[0046] Figure 3 It is a schematic diagram of the structure of setting up a double-layer sealing layer and an elastic layer.
[0047] The horizontal direction represents the lateral direction, and the vertical direction represents the thickness direction.
[0048] In the figure:
[0049] 1-support layer; 21-phase change layer; 22-first sealing layer; 23-second sealing layer; 3-conductive layer; 4-expansion buffer layer; 5-elastic layer. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0051] Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0052] In a first aspect, the present application discloses a composite current collector, comprising:
[0053] Support layer 1, the support layer is a porous support layer with a plurality of holes inside;
[0054] The conductive layer 3 is attached to the surface of the supporting layer 1;
[0055] And, a filling layer, which includes a phase change layer 21 and a closed layer 22 arranged on the outside of the phase change layer 21, the phase change layer and the closed layer can be a multi-layer structure, for example, the phase change layer includes a phase change layer of multiple components and different materials; wherein, an expansion buffer zone 4 exists on the side of the phase change layer 21 to provide a buffer zone for volume expansion during solid-liquid phase change.
[0056] Specifically, the thickness of the support layer 1 is 3.5-300 μm; the hole form of the support layer 1 can be a blind hole or a through hole formed on the support layer; preferably, the holes can be interconnected. At this time, illustratively, the support layer is set to a three-dimensional structure of foam metal, such as foam copper, foam aluminum, foam nickel, foam stainless steel, etc., with a porosity of 80%-95%, and the pore size of the porous material is 0.05-1 mm. The internal holes are mostly interconnected, which can reduce the weight of the support layer; the support layer can also be a metal mesh layer, at least one of aluminum mesh, copper mesh, nickel mesh, and stainless steel mesh. The mesh number is 80-1000 mesh. The setting of the porous material can increase the mutual mechanical interlocking with the filling layer and increase the anchoring force.
[0057] like Figure 1 , showing that a sealing layer is provided on both sides of the phase change layer 21; for the sealing layers 22 and 23, the material thereof is selected to be a polymer as the main carrier, so as to facilitate filling into the support layer; the relevant polymer material is an existing conventional polymer material, and as a preferred polymer material, PP and PET can be selected, which are composite current collector substrates with a large industrial use in the market, and of course other polymer substrates in the prior art can also be used;
[0058] Regarding the formation of the first sealing layer 22, after being bonded to the support layer 1, the polymer film is hot-pressed and composited at a temperature at or above the melting point (Tm), and then cooled. The hot-pressing pressure is exemplarily set to 0.5-1.5 MPa. Since the film thickness of the first sealing layer 22 is less than the thickness of the support layer, it is only partially embedded in the surface of the filling layer. The first sealing layer 22 is filled and composited by hot-pressing film, which can easily form local filling and also provides a fixed basis for the formation of the subsequent filling layer. Of course, a release agent can also be further coated on the composite side surface to prevent part of the filling layer material that is not completely filled into the support layer from being peeled off together with the release agent layer later.
[0059] The phase change layer 21 can be made of phase change wax, polyethylene wax, fatty acid, etc. with a certain phase change temperature. The phase change latent heat is preferably above 120 J / g, and the phase change temperature is 45-65°C. By selecting a relatively suitable phase change temperature, the phase change endothermic / exothermic can be achieved at a relatively safe temperature, thereby controlling the system temperature, especially the temperature near the current collector. At the same time, it can also reduce the number of volume increases caused by the melting phase change, reduce the frequency of volume expansion, and thus reduce the impact of expansion on the system; the thickness of the phase change layer 21 when solidified is 0.4-0.7 times the thickness of the filling layer;
[0060] In order to reduce the excessive volume change in the phase change layer 21 caused by the melting phase change, Figure 1The expansion buffer zone 4 is set as the gap between the phase change layer 21 and the sealing layer 22. The size of the gap is preferably set to 0.05-0.1 times the thickness of the phase change layer 21. At the same time, in some embodiments of the present application, the gap is set at only one place; of course, pores can also be set on both sides of the phase change layer 21.
[0061] When the phase change layer 21 is formed, it is preferably based on the method of cast coating. The above cast coating process and equipment are existing conventional coating methods and will not be described in detail. At this time, the key lies in the selection of the coating amount. Based on the thickness of the support layer and the pore specifications (size or porosity), the appropriate coating amount can be determined through a limited number of experiments to achieve local coating on the inner layer of the support layer; during coating, the temperature of the relevant polymer coating liquid should be kept above its melting temperature during the cast coating process to promote the coating gravity self-penetration effect, and then cooled to below the solidification point;
[0062] The second sealing layer 23 is formed by the same hot pressing process as the first sealing layer 22. The main difference is that in order to control the formation of the expansion buffer zone 4, a suitable thickness of the hot pressing film is selected, and auxiliary cooling measures can be added, such as bonding cooling rollers or entering a cooling environment (such as a cooling room) for air cooling to accelerate the solidification of the molten sealing layer to avoid the gaps in the expansion buffer zone 4 being covered by the molten liquid due to a long solidification time.
[0063] The material of the conductive layer 3 can be based on a vapor deposition process, such as evaporation and sputtering. Since the porous support layer is a conductive material, it can also be carried out by water electroplating. The material can be selected from copper, aluminum, nickel, chromium, etc., and its thickness is set at 0.1-2.0μm; the conductive layer can be set on one side or both sides of the support layer.
[0064] like Figure 2 ,and Figure 1 The main difference is that it shows the case where only one-side sealing layer is provided; in this case, the conductive layer 3 is preferably provided on the side where the sealing layer 22 is not provided, and after being deposited on the surface of the support layer 1, it also has a sealing effect and plays a certain sealing and barrier role. Therefore, the sealing layer also includes the conductive layer 3 formed on the surface of the support layer 1.
[0065] Reference Figure 3 , showing the situation of forming a double-sided expansion buffer zone 4 after preparation. As for the way of forming a gap, after phase change melting and re-solidification, it may be merged into a single-sided setting due to the gravity of the molten liquid.
[0066] In addition, the expansion buffer zone 4 can also be set as an elastic layer 5, and the elastic layer 5 has a low elastic modulus; it can provide a buffer space during the melting phase change, which can avoid to a certain extent the overall strength being affected by the setting of a gap and the absence of fillers in the porous supporting layer at the gap. At the same time, it can also make the internal filler have a good anchoring effect and is not prone to large slippage, thereby ensuring the overall uniformity of the film; preferably, the elastic modulus of the elastic layer 5 is less than or equal to 1000MPa, and more preferably less than or equal to 500MPa; the elastic layer can be selected from materials with low elastic modulus such as rubber, thermoplastics (elastomers), etc.
[0067] Of course, the expansion buffer zone 4 can also be configured such that the elastic layer 5 and the gap work together.
[0068] When forming the first elastic layer, the elastic particles can be dispersed in a solvent (such as an alcohol or ester solvent), and after the solvent is evaporated, the elastic particles are attached to the pore walls of the support layer 1 and the surface of the first sealing layer 22;
[0069] When further forming the second elastic layer, drying can be performed in a negative pressure environment to reduce the boiling point of the solvent to a certain extent. The boiling point is preferably lower than the phase change temperature of the phase change layer, which can promote the evaporation and discharge of the solvent. In addition, the solvent gas evaporated under vacuum will bring the elastomer particles to the surface of the phase change layer 21, and after cooling, the elastomer particles will be enriched on the surface of the phase change layer to form a second elastic layer. If necessary, a cooling zone can also be set on the side corresponding to the first sealing layer 22 to avoid the problem of melting of the first sealing layer 22 during processing and ensure the sealing property.
[0070] Figure 3 In the process of forming the second sealing layer 23 and the conductive layer 3, the formation is consistent with the above, and will not be repeated herein.
[0071] Preferably, a release layer is provided on the surface of the second sealing layer 2, and the thickness of the second sealing layer 23 on the other side of the phase change layer 21 is substantially consistent with the thickness of the remaining space of the support layer 1, and is slightly larger than the thickness of the remaining space, so that the pores can be substantially filled during hot pressing and compounding, and an extrusion force is provided to the internal filling layer, thereby increasing the filling density and improving the anchoring adhesion of the elastic layer. The small amount of remaining coating can be directly scraped off later to expose the support layer 1.
[0072] The release agent may be a release agent known in the art, for example, a silicone release agent, a fluorine release agent, and the like.
[0073] It should be noted that the above-mentioned filling layer may be composed of a plurality of groups of filling layers, and these filling layers may be of the same components or of different components, which should also be included in the protection scope of the present application.
[0074] The present application also discloses a composite current collector prepared based on the above preparation method, and an energy storage device based on the current collector, such as a lithium battery, the preparation method and process of which can be prepared according to the conventional lithium battery
[0075] In the description of the present invention, it is to be understood that the terms “center”, “longitudinal”, “lateral”, “length”, “width”, “thickness”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside”, “outside”, “clockwise”, “counterclockwise”, “axial”, “radial”, “circumferential”, etc., indicating orientations or positional relationships based on the orientations or positional relationships shown in the drawings or conventionally expressed in the prior art, are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0076] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0077] The term "multiple" as used in this application refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).
[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. The present application discloses a composite current collector, comprising: The support layer is a porous support layer having a plurality of holes inside; A conductive layer is attached to the surface of the support layer; and, a filling layer, which includes a phase change layer and a sealing layer arranged on the outer side of the phase change layer; The characteristic of the invention is that there is an expansion buffer zone on the side of the phase change layer so as to provide a buffer zone during the solid-liquid phase change.
2. The composite current collector according to claim 1, characterized in that: The total thickness of the expansion buffer is set to 0.05-0.1 times the thickness of the phase change layer.
3. The composite current collector according to claim 1, characterized in that: The expansion buffer is set to empty; And / or, the expansion buffer area is configured as an elastic layer, and the elastic layer is formed by evaporating a solvent of the elastic material under a vacuum environment.
4. The composite current collector according to claim 3, characterized in that: The thickness of the support layer is 3.5-300 μm; And / or, the pore size of the porous material is 0.05-1 mm.
5. The composite current collector according to claim 4, characterized in that: The holes in the support layer are blind holes or through holes; And / or, the holes of the support layer are interconnected.
6. The composite current collector according to any one of claims 1 to 5, characterized in that: The support layer is configured as a three-dimensional structured foam metal with a porosity of 80%-95%; Alternatively, the support layer is configured as a metal mesh layer.
7. The composite current collector according to claim 6, characterized in that: The phase change latent heat of the phase change layer is preferably above 120 J / g; And / or, the phase change temperature of the phase change layer is 45-65°C.
8. The composite current collector according to claim 7, characterized in that: The thickness of the phase change layer when solidified is 0.4-0.7 times the thickness of the filling layer; and / or, the phase change layer is formed in the support layer based on a casting method.
9. The composite current collector according to claim 8, characterized in that: The sealing layer material includes a polymer material; and / or, the sealing layer is compounded in the supporting layer based on a hot pressing method.
10. The composite current collector according to claim 9, characterized in that: The thickness of the conductive layer is 0.1-2.0 μm; the material of the conductive layer is one or a combination of copper, aluminum, nickel, chromium, gold, and silver.
Citation Information
Cited By
Phase change composite current collector and preparation method and application thereof
CN120511307A